Distinctive bronchial inflammation status in athletes: Basophils, a new player - Sastre, B.; Fernandez-Nieto, M.; Rodriguez-Nieto, M. J.; Aguado, E.; Sastre, J.; del Pozo, V. (European Journal of Applied Physiology, 2013)
The aim of the study was to establish bronchial inflammation status and to measure eicosanoids in sputum obtained from active elite athletes. A total of 68 subjects were enrolled. Twelve were non-athletes and non-asthmatic (NAtNAs), 21 non-athlete asthmatics (NAtAs), 11 athlete non-asthmatics (AtNAs), and 24 athletes with asthma (AtAs) with positive indirect or direct bronchial challenges. Induced sputum was used to measure cells and eicosanoids. Sputum differential cell counts in all the subject groups revealed eosinophilia with the exception of NAtNAs control subjects. Athletes with and without diagnosed asthma showed a significant increase in bronchial epithelial cells and lymphocytes present in their sputum. Also, flow cytometry revealed that a significantly higher number of basophils were present in sputum from athletes (without and with asthma) when compared with non-athletes (without and with asthma). Asthmatic athletes and non-athletes showed a higher increase in LTC4 levels and PGE2 metabolites in sputum when compared with healthy controls. The present study identifies basophils as a new player present in athletes bronchial inflammation defining athlete status and not necessarily associated with exercise-induced bronchoconstriction.